2004
DOI: 10.1002/cbic.200300669
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Labelled Thiourea‐Bridged Glycodendrons

Abstract: GlcNAc-coated glycodendrimers, which are polyvalent glycomimetics, display strong in vitro affinity for the rat natural killer cell protein-1A (NKR-P1A), a C-type lectin-like receptor of natural killer (NK) cells in rats, humans and some strains of mice. Administration of these compounds in vivo results in a substantial increase in the antitumour activity with involvement of the natural cell immunity. To clarify the in vitro and in vivo fate of these molecules, we synthesized labelled glycodendron analogues of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Animal model cells were studied by the group of Kren who described the activation of rat natural killer (NK) cells by glycodendrimers. [19] Another study by Lee et al reports on the grafting of multi-lineage haematopoietic factor human interleukin-3 (hIL-3) on a fifth-generation poly(amidoamine) PAMAM dendrimer. The in vitro immunostimulating properties of this conjugate were reported to be lower than those of free hIL-3.…”
mentioning
confidence: 99%
“…Animal model cells were studied by the group of Kren who described the activation of rat natural killer (NK) cells by glycodendrimers. [19] Another study by Lee et al reports on the grafting of multi-lineage haematopoietic factor human interleukin-3 (hIL-3) on a fifth-generation poly(amidoamine) PAMAM dendrimer. The in vitro immunostimulating properties of this conjugate were reported to be lower than those of free hIL-3.…”
mentioning
confidence: 99%
“…Among these architectural categories, glycodendrons were chosen for our study, because (i) a relatively large number of carbohydrates can be displayed with a high density, (ii) their valency and size can be easily adjusted, and (iii) they can be selectively functionalized for conjugation to other biomolecules. Over the past several years, many groups have found that glycodendrimers/ glycodendrons exhibit strikingly enhanced affinity against target proteins (23,31,32). More recently, different synthetic approaches and applications of these macromolecules have been explored (33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Several low molecular weight and low valence glycodendrimers (dimers, trimers and tetramers) are very potent and, sometimes, even more potent than higher valency analogs in their interaction with lectins. [4][5][6][7] This is very important from the medicinal chemistry point of view, since low molecular dendrimers are expected to have favorable physicochemical properties comparing to the high molecular weight, multivalent ones.…”
Section: Introductionmentioning
confidence: 99%